The Effect of Quality, Image and Price on Repurchase Decisions - Tridiar Antaka; Syanaz Iklima (FEBI UIN Sunan Kalijaga, 2021)
This research aimed to determine whether there is the influence of product quality, brand image and price towards the repurchase decision of smartphone xiaomi. This research uses quantitative method. The number of samples in this research was 100, this research used purposive sampling technique to determine the samples. Method of completion of data used in this research were a questionare and google form. Result of t test shows significant influence product quality variable on decision making with tcount 3.111 ≥ t-table 1.660. Significant influence brand image on decision making with tcount 3.153 ≥ t-table 1.660. Significant influence price on decision making with tcount 6.980 ≥ ttable 1,660. Product quality, brand image and price variables simultaneously have an effect of repurchase decision.